Early detections of SARS-CoV-2 in wastewater and their use in COVID-19 epidemiological control (Research, Society and Development, 2021)
SARS-CoV-2 is a new type of coronavirus that is capable to infect humans and cause the severe acute respiratory syndrome COVID-19, a disease that has been causing enormous impacts across the whole Earth. COVID-19 patients, including mild, pre-symptomatic and asymptomatic cases, were often seen to contain infectious fragments of SARS-CoV-2 in urine and feces samples. Thus, studies to detect the new coronavirus in wastewater, which collect and concentrate human excreta, have been extremely useful as a tool to monitor the virus spread in the communities. The surveillance, frequently used to elaborate economical non-invasive diagnoses about the circulation of chemicals and pollutants in populations, could be used as a quick alert about emerging and reemerging COVID-19 epidemics, improve the predictions concerning the SARS-CoV-2 dissemination and promote the development of better viral containment measures. Along that, the approach could be used to construct more accurately epidemiological models, foment better practices to coordinate resources an administer the vaccines, assess the propagation of SARS-CoV-2 variants across temporal and geographic scales, evaluate environmental risks and also the effectiveness of disinfection systems. In this review, it was addressed early reports regarding SARS-CoV-2 detections in wastewater and the importance of this valuable approach in the application of faster and more effective interventions from public health authorities, either towards the COVID-19 or any other epidemic disease in the future.